Catur Murti Counseling Construction Based on Adiluhung Noble Teachings of Raden Mas Panji Sosrokartono - Habsy, Bakhrudin All (Kuras Institute, 2024)
This study aims to foster and develop the discipline of counseling study with the name of Catur Murti counseling based on the material base of Indonesian culture developed with one of the most explicit ideas in the Javanese literary tradition, which is a collection of valuable teaching in seat-seat (letters) of Raden Mas Panji Sosrokartono. Catur Murti counseling construction presents a form of development of culture-based counseling, which fulfills the postulates of the rules of scientific discipline, namely internal coherence, its correspondence with reality, and its functionalities when applied theoretically and practically. This study uses a qualitative approach with hermeneutics type to understand the text in the Javanese literary tradition. The study's findings show coherence that is interrelated and mutually reinforcing between the relationship of each element, the main concepts, and the meaning of the adiluhung noble teaching of Raden Mas Panji Sosrokartono as part of a systematic counseling theory. Catur Murti's counseling systematic consists of the main concepts as follows: (1) Basic philosophy, which is classified into: (a) Developmental history, (b) Human nature, (2) The main concepts, which are classified in: (a) Structure and development of human personality, (b) Healthy and unhealthy state of person, (3) The purpose of counseling, (4) Counseling relationships, which are classified in: (a) Attitudes, roles, and duties of the counselor, (b) Attitudes, roles and duties of the counselee, (5) Mechanisms of change, which are classified in (a) Counseling techniques, (b) Counseling stages.